The Influence of Multiple Role Conflict on the Performance of Female Health Workers With Job Stress as a Mediation Variable - Muhamad Kahfi Fadilah; Sabrina Dinda Triana; Anna Suzana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Dual roles are often one of the main causes of work istress, especially fori women. When someone has to divide their time and energy, they may feel overwhelmed and have difficulty meeting all the demands. Conflict between these roles can cause stress, anxiety, and fatigue. The main objective of this study was toI clarify the relationship between dual role conflict, job stress, Iand performance among femaleI health workers. TheI method used in this studyI is a quantitative approach with a survey method, then the dataI analysisI techniqueI used is the SEM-PLS dataI analysis technique. BasedI onI theI data that has been obtained, the sample used in this study was 100 female civil servant health worker respondents. The results obtained are thatI there is a significantI positive effectI of dualI role conflict onI work stress of 0.472. InI addition, there is a significantI negative effect on the relationship between dual role conflict and performance of -0.411. Then, there is a significant negative effect on the relationship between work stress and performance of -0.489. And it is also known that the work stress variable significantly acts as a mediating variable on the effect of dual role conflict on performance of -0.231.